2015
DOI: 10.1101/gad.255182.114
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin signatures of cancer

Abstract: Changes in the pattern of gene expression play an important role in allowing cancer cells to acquire their hallmark characteristics, while genomic instability enables cells to acquire genetic alterations that promote oncogenesis. Chromatin plays central roles in both transcriptional regulation and the maintenance of genomic stability. Studies by cancer genome consortiums have identified frequent mutations in genes encoding chromatin regulatory factors and histone proteins in human cancer, implicating them as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
174
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(175 citation statements)
references
References 141 publications
(186 reference statements)
1
174
0
Order By: Relevance
“…2A). H3K27 acetylation and methylation are mutually exclusive, and the acetyltransferase CBP/p300 complex and methyltransferase Polycomb repressive complex (PRC2) act in opposition to one another (24,25 decrease in H3K27ac, we analyzed the expression of CBP/p300 and PRC2 components in H3122-LR cells using qRT-PCR (Fig. 2B).The mRNA expression of CREBBP and EP300 were decreased in H3122-LR cells, suggesting that the global decrease in H3K27ac levels was at least partially due to the decreased expression of H3K27 acetyltransferase.…”
Section: Massive Enhancer Remodeling Accompanies Acquired Resistancementioning
confidence: 99%
“…2A). H3K27 acetylation and methylation are mutually exclusive, and the acetyltransferase CBP/p300 complex and methyltransferase Polycomb repressive complex (PRC2) act in opposition to one another (24,25 decrease in H3K27ac, we analyzed the expression of CBP/p300 and PRC2 components in H3122-LR cells using qRT-PCR (Fig. 2B).The mRNA expression of CREBBP and EP300 were decreased in H3122-LR cells, suggesting that the global decrease in H3K27ac levels was at least partially due to the decreased expression of H3K27 acetyltransferase.…”
Section: Massive Enhancer Remodeling Accompanies Acquired Resistancementioning
confidence: 99%
“…Recent cancer genome sequencing approaches of many types of primary tumors and cancer cell lines have revealed that MLL3 and MLL4/COMPASS are among the most frequently mutated genes in both solid tumors and hematological malignancies (Morgan and Shilatifard 2015). The MLL3 mutation or its deletion is found in hematological malignancies, including 15% of DLBCL, MDS, and AML (Mrozek 2008;Pasqualucci et al 2011;Zhang et al 2013).…”
Section: Mutations Of Mll3 and Mll4 Members Of The Compass Family Inmentioning
confidence: 99%
“…Thus, caution should be used in equating the regulatory role of a chromatin-modifying enzyme to a particular histone PTM. Reflecting their key role in gene control, cancer genome sequencing studies revealed that chromatinmodulating enzymes are frequently mutated in human cancers (Laugesen and Helin 2014;Masliah-Planchon et al 2015;Morgan and Shilatifard 2015).…”
Section: Shmtmentioning
confidence: 99%